Study of clinical and radiological profile of children with neurocysticercosis - Pandit, Manjunath Suresh; Sharma, Jagadish Narayan; Choudary, Anita; Vijay, Priti (International Journal of Contemporary Pediatrics, 2017)
Background: To study the clinical and radiological profile of children with Neurocysticercosis Hospital based, Observational study conducted in SPMCHI, Jaipur from June 2015 to June 2016. Methods: 50 children diagnosed of neurocysticercosis based on clinical features and findings on magnetic resonance imaging with contrast were enrolled while excluding the other common causes of granuloma. Results: A total of 50 children completed this study. Mean age of the presentation was 8.68±2.133 (5 to 16) years, with an M: F of 0.92:1. Overall patients presented with generalized seizure in 76%, focal in 16%, headache±vomiting in 6%, focal neurodeficit in 2% and combination of symptoms in 60.5% cases. MRI brain showed a solitary lesion in 45 (90%) and multiple in 5 (10 %). At presentation lesions were vesicular in 46 %, nodular calcified in 16 %, granular nodular in 10 %, colloidal vesicular in 6% and mixed in 6%. One child presented with a starry sky appearance. Conclusions: Neurocysticercosis usually affects young persons, youngest age of presentation 5 years, was found more common among vegetarians. Most common clinical manifestation is seizures. Single lesion is more common than multiple lesions, commonly presenting in vesicular stage. NCC should be considered first in the differential diagnosis of new-onset seizure among the children of developing countries, where taeniasis is endemic.